Selective Recognition of Kanamycin via Molecularly Imprinted Nanosensor - Esma Sari (Hittite Journal of Science and Engineering, 2022)
Herein, the molecular recognition sites on the surface of the chip were created by the molecular imprinting method to produce the surface plasmon resonance (SPR) based nanosensor for the real-time kanamycin (KAN) detection. Firstly, kanamycin imprinted nanofilm, which has specific recognition cavities for kanamycin were synthesized by in-situ radical polymerization. Fabricated nanofilm for the detection of kanamycin was characterized with FTIR, ellipsometer, and atomic force microscope by the means of structurally and morphologically. The mean thickness values were determined for the imprinted and non-imprinted nanofilms as 102.4±3.1 nm and 101.8±4.7, respectively. The sensitivity performance of imprinted nanosensor was investigated by using the KAN solutions at different concentrations (25-200 ng/mL). The refractive index and the KAN concentration were found to be in perfect agreement with a regression coefficient (R2, 0.992). The detection limit was calculated as 0.40±0.05 ng/mL by using the equation in the calibration curve. The response of imprinted and nonimprinted nanosensors towards the chemical analogs of KAN (NEO and SPM) were investigated to prove the selectivity of KAN imprinted nanosensors. The reusability performance of imprinted nanosensor was investigated by spiking 25 ng/mL KAN solution with three replicates. When the kinetic analyzes were examined, high sensitivity real-time kanamycin analysis was performed at very low concentrations with good reusability.